General concepts of "Achromatic", "Chromatic", "Primary", "Brick" and "Additional" colors in visual arts - Adhamova Oltinoy Rafiqjon's Qizi (Genius Journals, 2023)
This article provides general information about achromatic, chromatic, warm and cold, primary and secondary colors taught in color science, which is considered a branch of fine art, comments on colors, and for brush owners describes a wide range of knowledge and skills related to working with color in the creative process.
Keywords: Uzbekistan; education; visual arts; color